188 Disarming the bomb in AL amyloidosis: a case report. (8th December 2021) - Licchelli, Luca; De Michieli, Laura; Sinigiani, Giulio; Da Pozzo, Stefano; Barbera, Mila Della; Rizzo, Stefania; Cecchin, Diego; Berno, Tamara; Cipriani, Alberto
Abstract: Aims: Light-chain amyloidosis (AL) is a rapidly progressive systemic disease commonly involving also the myocardium, with poor outcome if lately diagnosed and treated. Clinical presentation can be widely varied, ranging from unapparent disease with soft symptoms to acute heart failure syndromes, requiring urgent therapies and supports. Methods and results: A 52-year-old women came to our outpatient cardiomyopathy clinic because of hypertrophic cardiomyopathy (HCM) suspicion. Family history included a paternal cousin with diagnosis of unspecified cardiomyopathy and cardiac arrest. Her medical history was unremarkable until few months ago, when she started to complain with palpitations and asthenia. Given that both electrocardiogram and echocardiogram had previously showed signs of left ventricular (LV) hypertrophy, she was referred to us for HCM evaluation. Our physical examination was unremarkable, in particular there were no signs of central or peripheral venous congestion. Electrocardiogram showed a diffuse strain pattern with inferolateral ST-depression and T-wave inversion. Echocardiogram showed a thicked interventricular septum (17 mm), a pseudo-normal transmitral filling pattern with mild increase of LV filling pressure ( E / E ′ 11), a severely dilated left atrium (51 ml/mq). To complete the diagnostic path for HCM, we asked for a cardiac magnetic resonance (CMR), which two months later gave to us the diagnosis of myocardial amyloid infiltration. The diagnosis was quite surprising, because the patient was fine, 6 min walking test assessed a good functional capacity (500 m), no heart failure signs were recorded. So, we sent the patient to perform bone scintigraphy, which showed Perugini 0 uptake, and blood exam, showing, instead, rise of lambda free light chains, cardiac troponin (41.5 ng/l) and NTproBNP (5318 ng/l). Patient was urgently referred to haematologists, who using bone marrow and fat pad biopsy diagnosed a multiple myeloma with stage IV sec. Mayo AL amyloidosis. (Cy)BorD therapy was started, reaching a complete response in 4 months. Conclusions: Diagnosis of AL amyloidosis is tricky due to heterogeneous clinical onset and multi-organ involvement. Cardiologist community should be aware of this condition, phenotypically mimicking HCM, but with very different management, in order to favour early diagnosis, prompt referral and treatment initiation. This case teaches that only 1. clinical awareness and 2. multidisciplinary approach can lead to disarm the bomb in AL amyloidosis.